Assessing commonality in liquidity with principal component analysis: The case of the Warsaw Stock Exchange - Joanna Olbryś; Elżbieta Majewska (Journal of Risk and Financial Management, 2020)
The studies concerning commonality in liquidity on emerging markets in Central and Eastern Europe are scarce and, in particular, they do not utilize the Principal Component Analysis (PCA) to identify latent factors in liquidity. Therefore, the main aim of this research is to assess commonality in liquidity on the Warsaw Stock Exchange (WSE) with the use of the PCA to extract common components of liquidity across a sample of stocks, and from a set of several liquidity proxies. The robustness tests within the whole sample and sub-periods are provided. The PCA results reveal that common latent factors in liquidity estimates exist on the Polish stock market, and three principal components are sufficient to substitute for the seven liquidity proxies utilized in this research. The regressions using these three principal components of liquidity proxies as latent factors in the market model of liquidity indicate no evidence of co-movements in liquidity on the WSE. The results are homogenous for all investigated periods so no reason has been found to reject the research hypothesis that commonality in liquidity does not exist on the Polish stock market. To the best of the authors' knowledge, no similar research has been conducted for the WSE thus far.
Keywords: 330; market microstructure; high-frequency data; daily data; commonality in liquidity; PCA; GARCH; Warsaw Stock Exchange